US State Cannabis Policy Bundles Dataset - Lilliard E. Richardson; Daniel J. Mallinson; Shazib Altaf; Grant Neeley (Scientific Data)
Abstract Cannabis policies across the U.S. states vary considerably, and we categorize state data into three policy bundles: pharmaceutical, permissive, and fiscal. Each of the bundles is comprised of twelve constituent policies that reflect the dimensions of state cannabis policy. Factor analysis confirmed the three policy dimensions, and the bundles for each state in each year were transformed to range from 0 to 100. This results in two datasets – one with the original 36 dichotomous policy indicators and one with the three policy bundles for each state from 1994 to 2023. The bundles provide researchers with data to understand the effects of cannabis legalization on myriad policy outcomes (e.g., public health or crime). The bundles capture significant variation in policy design cross-sectionally between the states and within the states over time. This provides an advancement over studies that treat legalization as a dichotomy, thus ignoring variation in policy design that is inherently related to impacts of interest, such as health, crime, and social outcomes.